2017
DOI: 10.1177/1759091417720582
|View full text |Cite|
|
Sign up to set email alerts
|

Nicotinic Receptor Abnormalities in the Cerebellar Cortex of Sudden Unexplained Fetal and Infant Death Victims—Possible Correlation With Maternal Smoking

Abstract: Nicotinic acetylcholine receptors (nAChRs) are cationic channels of the neuronal cell membrane, differentially expressed in the central nervous system which, when activated by endogenous acetylcholine or exogenous nicotine, are able to enhance cholinergic transmission. The aim of this study was to investigate in human perinatal age the immunohistochemical expression of the α7-nAChR subtype, given its involvement in neuronal differentiation and its significant vulnerability to the toxic effects of nicotine. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…This study highlights for the first time the important involvement of the SNpc in SIDS pathogenesis and, as already reported in our previous studies (43)(44)(45)(46)(47)(48)(49), confirms that cigarette smoke absorption may have strongly influenced the results here presented. In fact, all the SIDS cases with decreased neuronal density, negative TH and NM expression and with mitotic neurons in the SNpc were born to smoking mothers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study highlights for the first time the important involvement of the SNpc in SIDS pathogenesis and, as already reported in our previous studies (43)(44)(45)(46)(47)(48)(49), confirms that cigarette smoke absorption may have strongly influenced the results here presented. In fact, all the SIDS cases with decreased neuronal density, negative TH and NM expression and with mitotic neurons in the SNpc were born to smoking mothers.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, in our SIDS cohort, a very low expression of the TH enzyme, indicative of DA deficit, was detected in 80% of cases with proven nicotine absorption. Our previous SIDS studies revealed a close correlation between maternal smoking, especially during pregnancy, and defects in the morphological/functional development of various nervous system structures (43)(44)(45)(46)(47)(48)(49). This study enhances our knowledge on the devastating effect of cigarette smoking and reinforces our awareness that once nicotine crosses the blood-brain barrier, it can harm and disactivate important brain centers which are crucial to perform the vital activities.…”
Section: Discussionsupporting
confidence: 73%
“…Other sections were saved and stained as deemed necessary for the morphometric evaluations, as indicated later, and also for further investigations, such as the immunohistochemical characterization of specific receptors that are differently expressed in sudden perinatal death victims and controls. [20][21][22]…”
Section: Neuropathologic Analysismentioning
confidence: 99%
“…Accordingly, experimental studies have shown that in utero exposure to maternal smoking is associated with neuronal mitotic abnormalities and increased programmed cell death with consequent reduction of the neuronal content (Roy et al, 1998;Chatterton et al, 2017). Moreover, our previous SIDS studies revealed a close correlation between maternal smoking during pregnancy and defects in the morphological/functional development of various nervous system structures (Lavezzi et al, 2010(Lavezzi et al, , 2012(Lavezzi et al, , 2013b(Lavezzi et al, , 2013c(Lavezzi et al, , 2017Lavezzi, 2018). This study enhances our knowledge on the devastating effect of cigarette smoking and reinforces our awareness that once nicotine crosses the blood-brain barrier, it can harm and deactivate important brain centers which are crucial to perform the vital activities.…”
Section: Discussionmentioning
confidence: 96%